Generics and the specific features of their regulation - E. A. Ushkalova; S. K. Zyryanov; A. V. Ushkalova (Неврология, нейропсихиатрия, психосоматика)
The article discusses the factors that influence the efficacy and safety of generic drugs, including regular generics, biosimilars, and generic nonbiological complex drugs. It emphasizes the importance of adequate regulatory requirements to provide a comparable therapeutic efficacy and a comparable cost-effectiveness ratio for generics versus brand-name drugs.